La fatigue musculaire altère la simulation mentale du mouvement - Demougeot, L.; Crognier, L.; Papaxanthis, C. (Science et motricité, 2011)
Mental simulation is a central process. However, the contribution of peripheral system is unclear. Executed and imagined movement durations were recorded in eight subjects before and after a fatiguing exercise of right arm. Duration of executed movement, after fatiguing exercise, significantly decreased (14.4%; P < 0.001) while it significantly increased (12.6%; P < 0.001) for the imagined movements. This difference would be explained by the lack of movement feedback during the mental simulation.